Fluktuasi Harga Saham Batu Bara: Peran Faktor Spesifik dan Makroekonomi - Ummi Khusnul Habibah; Idah Zuhroh; Dhurotus Sangadah (Universitas Muhammadiyah Malang, 2022)
This study aims to analyze the effect of specific faktor (profitability, leverage, EPS) and makroeconomic factor (inflation , PDB) on the variable stock price. Using the financial reports of mining companies in the coal company, we take specific factor data (profitability/ROA, leverage/DER), EPS), Macroeconomic factor (Inflation, PDB) and stock price (closing price) from 10 companies, which were selected as samples, from 2011 to 2020. Data was analyzed using the Regression analysis panel data method. The results show that ROA, DER, EPS, Inflation, PDB affect changes in stock prices. The implication of this research is to provide knowledge to investors about the importance of knowing the company’s financial performance. Companies with good financial performance will easily develop because there are sufficient funds for company operations. By analyzing financial ratios, investors can get signals to decide whether to invest in the company they want.